If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.25(40 + -8x) = 19x + 2 + -5x (40 * 0.25 + -8x * 0.25) = 19x + 2 + -5x (10 + -2x) = 19x + 2 + -5x Reorder the terms: 10 + -2x = 2 + 19x + -5x Combine like terms: 19x + -5x = 14x 10 + -2x = 2 + 14x Solving 10 + -2x = 2 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 10 + -2x + -14x = 2 + 14x + -14x Combine like terms: -2x + -14x = -16x 10 + -16x = 2 + 14x + -14x Combine like terms: 14x + -14x = 0 10 + -16x = 2 + 0 10 + -16x = 2 Add '-10' to each side of the equation. 10 + -10 + -16x = 2 + -10 Combine like terms: 10 + -10 = 0 0 + -16x = 2 + -10 -16x = 2 + -10 Combine like terms: 2 + -10 = -8 -16x = -8 Divide each side by '-16'. x = 0.5 Simplifying x = 0.5
| 2-8/7-3 | | (2y+11)=4(4y+2) | | 4-2/9-1 | | 8=8+3a+8a | | 570-c=4.75 | | .1(2.5y-6)=.4(6y+7) | | y=h^3+9h^2+14h-72 | | W+5=0 | | 4.75+c=570 | | (3-4)+18*45=n | | 2.5n-3=-15 | | -x+2=2x+1 | | 8(c+12)=6(c+10) | | 28+27m=35+20m | | -n+2n=9 | | 15b-8=-b-12 | | 1(2m-16)=1(2m+4) | | 2x/7=6/21 | | -2a-7(5a+4)= | | x=y*(10-2y) | | 29x+19y=-23 | | -8g+48=-3g+7g | | 3x^2-2kx+k=0 | | -n+-2n=9 | | y=-3(3/4)-3 | | X/7-6=1 | | -n+-2n=8 | | -7g+16=-7g+4g | | 4-3x=6x+10 | | -3g+15=-5g+7g | | y+y-12.6=-10 | | .217+j=4.11 |